Efektivitas Alat Pengolahan Sampah Plastik Jenis Low Density Polyethylene dan Polyethylene Terephthalate dengan Metode Pyrolisis - Manarul Ikhsan; I Putu Widiantara; Mega Trishuta Pathiassana (Universitas Hamzanwadi, 2021)
Excessive usage of plastic has threatened not only environment but also human health if it is managed poorly. One of the solutions to manage plastic waste is through process of pyrolysis. A processing of plastic waste through pyrolysis is suggested where such process transform plastic waste into usable output of liquid, gas, and solid. Additionally, such process sorts out the liquid output into a number of characteristics thorugh faucet 1, faucet 2, and faucet 3. In this experiment, low density polytethylene (LDPE) and polyethylene terephtalate (PETE) were used. Process of pyrolysis were carried out at temperatures of 100 and 140 °C and at processing time of 30, 60, and 90 minutes. It was found that for both plastics, the best condition to obtain maximum output of liquid through condensation of steam/gas were 140 °C for 90 minutes. Although the production of large liquid output was effectively done by using PETE (574 gram) than that of LDPE (197 gram). The output of LDPE may effectively result in liquid with clear appearance through faucet 1. Output of solid from LDPE was more tough than that of PETE. Output of gases from LDPE exhibited better combustion as compared to PETE.